Analisis Sistem Manajemen Keselamatan Dan Kesehatan Kerja Pada Proyek Pembangunan Perpustakaan Habibie Kota Parepare - Nurul Patria; Hamka Hamka; Andi Bustan Didi (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The various building failures show that there are still many construction safety problems that are being ignored so that the Habibie library building construction project in Parepare City cannot be separated from these threats. Implementation of the Occupational Safety and Health Management System (SMK3) needs to be held to this construction project to prevent, reduce, and even strive to eliminate the risk of work accidents (zero accidents). The aim of this research is to analyze the level of success of the SMK3 and factors causing the delay of its implementation. This study using a descriptive method with qualitative approach through distributing questionnaires to 150 respondents which later be analyzed using SPSS program. The research results show that the success rate for implementing occupational safety and health is 74.20% and the most influential inhibiting factors are limited funds and also the lack of knowledge about SMK3 from the company and its employees.